2020
DOI: 10.33371/ijoc.v14i4.818
|View full text |Cite
|
Sign up to set email alerts
|

Update on Diagnosis of Childhood Acute Lymphoblastic Leukemia (ALL) in Indonesia

Abstract: Childhood cancer has been a global public health scourge with considerably escalating incidence each year [1]. Although the incidence is relatively lower compared to adult malignancies, it remains the leading cause of disease-related death in children. The most frequent childhood cancer is acute lymphoblastic leukemia (ALL) with an annual incidence of 3.5 per 100,000 children in the United States [2]. Similarly, in Indonesia, ALL has the highest number of cancer cases in children [3]. The total incidence of AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…The population studied were all children (0–18 years old) diagnosed with acute lymphoblastic leukemia. Molecular and cytogenetics studies were very limited in Indonesia [ 11 ]. Therefore, the diagnosis must be confirmed by a minimum of a bone marrow smear with immunophenotyping analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The population studied were all children (0–18 years old) diagnosed with acute lymphoblastic leukemia. Molecular and cytogenetics studies were very limited in Indonesia [ 11 ]. Therefore, the diagnosis must be confirmed by a minimum of a bone marrow smear with immunophenotyping analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, the exact incidence rate of childhood ALL in Indonesia is still unknown. A frequently mentioned incidence of childhood ALL is 2.5 to 4.0 new cases per 100,000 children in Indonesia [ 10 , 11 ]. However, upon tracing the literature, the original source states that the incidence mentioned is only an estimation and that "there was no international or national publication on the incidence of childhood cancer and childhood leukemia in Indonesia" [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfavorable results were reported in Indonesia. Studies from Jakarta and Yogyakarta reported 5-year survival rates of 28.9% and 31.8%, respectively [11].…”
Section: Discussionmentioning
confidence: 99%
“…The difference in outcomes between Indonesia and other countries may be due to the high rate of relapse and death during treatment. Several studies reveal that the factors that influence the poor outcome of ALL in children in developing countries are inadequate facilities, delayed diagnosis, limited access to health care, neglect of treatment, and suboptimal supportive care [11].…”
Section: Discussionmentioning
confidence: 99%
“…Quality of Life of Parents with ALL Children survival rates of 28.9-31.8%, 69.4%, and 55.1% for children with acute lymphoblastic leukemia (ALL) in Indonesia, Malaysia, and Thailand, respectively. The challenges of intensive treatment and low survival rates influence the quality of life of parents [9,10]. Several factors, namely age, sex, education, economic status, beliefs, duration of care, mental health, and family functioning, influence the quality of life of parents raising children with ALL [10,11].…”
Section: I C H E L L E T R I S Y a E T A Lmentioning
confidence: 99%